ASSESSMENT OF SOME HEAVY METALS CONCENTRATION IN LETTUCE (Lactuca sativa [L.,]) CULTIVATED ALONG HIGHWAY IN ZARIA, NIGERIA - N. M., IBRAHIM; ZAKARI, H. H.; NEGBENEBOR, H. E.; ADEIZA, Z. O.; NURA, S. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Urban roadside soils are known to be the primary "recipients" of significant levels of heavy metals from a range of sources. Due to the possible negative ecological impacts of heavy metals, contamination of agricultural soil by these substances has become a serious environmental concern. The aim of this study was to determine the levels of certain heavy metals in lettuce grown alongside highway in Zaria, Nigeria. The soil and plant samples were collected at different distances from the roadside at two different locations namely: Marabar yakawada and Bomo farms (control). Atomic absorption spectrophotometer was used in the determination of the metal ions (Pb, Mn, Cd and Cr) concentration. The range of the concentration levels in Lactuca sativa in marabar yakawada and bomo were Pb (7.56 - 18.25mg/kg), Mn (2.06 - 6.46mg/kg), Cd (0.39 - 1.05mg/kg) and Cr (0.11 - 0.28mg/kg), and in soil were Pb (8.08 - 46.60mg/kg), Mn (3.97 - 11.30mg/kg), Cd (1.05 - 2.93mg/kg) and Cr (0.43 - 2.08mg/kg). Pb, Mn and Cd in lettuce were above the permissible limit set by FAO/WHO while Cr was below. The highest metal concentration suggests anthropogenic origins which confirm the effect of vehicular emissions on the roadside environment.